2006
DOI: 10.1111/j.1745-7254.2006.00255.x
|View full text |Cite
|
Sign up to set email alerts
|

Progress in studies of huperzine A, a natural cholinesterase inhibitor from Chinese herbal medicine1

Abstract: Huperzine A (HupA), a novel alkaloid isolated from the Chinese herb Huperzia serrata, is a potent, highly specific and reversible inhibitor of acetylcholinesterase (AChE). Compared with tacrine, donepezil, and rivastigmine, HupA has better penetration through the blood-brain barrier, higher oral bioavailability, and longer duration of AChE inhibitory action. HupA has been found to improve cognitive deficits in a broad range of animal models. HupA possesses the ability to protect cells against hydrogen peroxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
223
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 416 publications
(230 citation statements)
references
References 125 publications
(173 reference statements)
3
223
0
1
Order By: Relevance
“…However, the swimming time in the target quadrant was greatly pro- npg longed in the probe trial in this group; this may suggest that the sample size for behavioral testing should be increased and that further refinements to the dosages need to be considered. Huperzine A (HupA), a lycopodium alkaloid isolated from Huperzia serrata (Qian Ceng Ta), has been widely used for AD (Alzheimer's disease) therapy in China and has been shown to enhance memory, cognitive skills and daily life capabilities in both AD and VD (vascular dementia) patients [22] . Using HupA as a positive control, we discovered that the action of PGS32 on the cognitive function of scopolamine-treated mice was comparably good; this suggested that PGS32 has as much promise as a potential cognition-enhancing therapeutic drug Figure 4.…”
Section: Discussionmentioning
confidence: 99%
“…However, the swimming time in the target quadrant was greatly pro- npg longed in the probe trial in this group; this may suggest that the sample size for behavioral testing should be increased and that further refinements to the dosages need to be considered. Huperzine A (HupA), a lycopodium alkaloid isolated from Huperzia serrata (Qian Ceng Ta), has been widely used for AD (Alzheimer's disease) therapy in China and has been shown to enhance memory, cognitive skills and daily life capabilities in both AD and VD (vascular dementia) patients [22] . Using HupA as a positive control, we discovered that the action of PGS32 on the cognitive function of scopolamine-treated mice was comparably good; this suggested that PGS32 has as much promise as a potential cognition-enhancing therapeutic drug Figure 4.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have suggested that huperzine A can improve mitochondrial dysfunction [90] and regulate anti-oxidative enzyme activities and apoptotic gene expressions [91] in ischemic animal models. Whether these effects contribute to VaD therapy and reflect responsible cellular targets remain open questions.…”
Section: Acetylcholinesterase Inhibitorsmentioning
confidence: 99%
“…Multiple lines of evidences proved that huperzine A is a mixed-competitive and reversible AChE inhibitor, which shows higher potency and selectivity of AChE inhibition both in vitro and in vivo as compared with galanthamine, donepezil, tacrine, and rivastigmine (reviewed by [2] ). The potent inhibitory effect on AChE could in turn markedly enhance the synaptic ACh release and consequently cholinergic neurotransmission.…”
Section: Multifaceted Pharmacological Effects Of Huperzine A: Cholinementioning
confidence: 99%
“…Since then, large amount of clinical studies have shown that huperzine A administration can significantly improve the memory, cognitive skills, and daily life abilities of AD patients with no severe side effects. Besides being indicated for AD, huperzine A is also used in treating memory impairment in vascular dementia (VaD) patients, schizophrenia patients and sleep disorder in insomniacs (reviewed by [2] ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation